"The medicine from behind": The frequent use of enemas in western African traditional medicine. (4th November 2015) - van Andel, Tinde; van Onselen, Sabine; Myren, Britt; Towns, Alexandra; Quiroz, Diana
Abstract: Ethnopharmacological relevance: Purgative enemas form an integral part of African traditional medicine. Besides possible benefits, serious health risks of rectal herbal therapy have been described in literature. To design appropriate health education programs, it is essential to understand traditional herbal practices and local perceptions of health and illness. Little is known about the herbal ingredients of enemas in Sub-Saharan Africa and consumers' personal reasons to use them. Aim of the study: To analyze the importance of enema use with regard to plant species used and illnesses treated in West and Central Africa, to understand the local health beliefs that underlie frequent enema use and to evaluate which recipes and practices could be beneficial or harmful. Materials and methods: We extracted data from 266 ethnobotanical questionnaires on medicinal (in particular women's health and childcare) and ritual plant use in Ghana, Benin and Gabon. Plants mentioned during interviews were vouchered and identified in herbaria. Health issues treated by means of enemas were ranked according to the number of plant species used for a specific illness. We compared our results with findings of medical research on benefits and risks of enema use in Sub-Saharan Africa. Results: We recorded ca. 213 different plant species used in hundreds of recipes for rectal insertions, mostly in Ghana and Gabon. Stomachache, abdominal pain, female infertility and birth facilitation were treated with the highest number of plants species. Cleansing the intestines of young children to promote their health by getting rid of 'dirt', instead of treating constipation, was an important cultural practice that required the rectal application of herbal medicine, as well as other cultural bound health issues like stimulating children to walk at an early age. Tradition, the bitter taste of herbal medicine and the rapid effect of enemas were frequently mentioned reasons for enema use. Discussion and conclusions: Literature indicates that although enemas can help to improve the hygienic conditions of a household with young infants, frequent enema use can pose serious risks like direct toxicity caused by harmful ingredients, mechanical injury and infections. In Africa, enemas containing herbal medicine are common methods of administering herbal medicine for a variety of diseases, rather than just medicinal treatments for constipation as previously thought. Health professionals should be aware of the extent of, and motivation behind enema use to develop culturally appropriate education programs, especially targeted at vulnerable groups such as elderly people, parents of young infants and pregnant women. Graphical abstract: